Long term renal outcome of childhood haemolytic uraemic syndrome - Fitzpatrick, M M; Shah, V; Trompeter, R S; Dillon, M J; Barratt, T M (BMJ, 1991)
OBJECTIVE--To evaluate the long term outcome of renal function in infants and children after diarrhoea associated haemolytic uraemic syndrome. SETTING--The Hospital for Sick Children, Great Ormond Street, and the Royal Free Hospital, London. SUBJECTS--103 children with the syndrome who presented between 1966 and 1985; 88 attended for follow up investigations (40 male, 48 female) with a mean age 11.6 (range 5.2-22.6) years and a mean duration of follow up of 8.5 (range 5.1-21.3) years. MAIN OUTCOME MEASURES--Blood pressure, ratio of early morning urine albumin to creatinine concentration, glomerular filtration rate, and plasma renin activity. RESULTS--The mean (SD) systolic blood pressure standard deviation score was 0.38 (0.67) and diastolic blood pressure SD score was 0.10 (0.76). The geometric mean ratio of overnight urine albumin to creatinine concentration was 1.27 (range 0.03-48.2), significantly higher than the value observed in 77 normal children (0.32 (0.05-1.95), p less than 0.0001). Glomerular filtration rate estimated from the plasma clearance of chromium-51 EDTA was 95.1 (22.7) ml/min/1.73 m2 surface area, and 16 children had a rate of less than or equal to 80 ml/min/1.73 m2. Significant negative correlations were found between glomerular filtration rate and urinary albumin to creatinine ratio (r = -0.41, p less than 0.0001) and glomerular filtration rate and systolic blood pressure SD score (r = -0.48, p less than 0.0001). A significant positive correlation was found between urinary albumin to creatinine ratio and systolic blood pressure SD score (r = 0.25, p = 0.02). CONCLUSIONS--After an acute episode of diarrhoea associated haemolytic uraemic syndrome 31% (27/88) of children had an increased albumin excretion, 18% (16/88) had a reduced glomerular filtration rate and 10% (9/88) had both, in association with a higher systolic blood pressure, indicating considerable residual nephropathy in this group.